2012
DOI: 10.1159/000343573
|View full text |Cite
|
Sign up to set email alerts
|

Subablative Er:YAG Laser Effect on Enamel Demineralization

Abstract: Objectives: To characterize the cariostatic potential of a low-energy Er:YAG laser treatment. Methods: Twelve sound premolars were selected. Two 2 × 1 mm windows were created on each tooth and randomly assigned to L1 and L2 groups. Three sites in each window were chosen with the middle site as the control and the left and right ones receiving Er:YAG laser treatment of 5.1 J/cm2 (L1) or 2.0 J/cm2 (L2), respectively. The teeth were further subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 43 publications
0
36
1
1
Order By: Relevance
“…When using Er:YAG laser with subablative parameters, it is very important to use the lowest energy level because higher energies produce microcracks and damage the peripheral and underlying tissues. 18 Therefore, subablative irradiation in this study was carried out with a very low energy level. Considering the promising outcomes of this study, cavity preparation with Er:YAG laser could be considered as a viable alternative to the conventional application of high speed handpiece and burs, which enhances the mechanical and compositional properties of lased dentin, especially when combined by subablative irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using Er:YAG laser with subablative parameters, it is very important to use the lowest energy level because higher energies produce microcracks and damage the peripheral and underlying tissues. 18 Therefore, subablative irradiation in this study was carried out with a very low energy level. Considering the promising outcomes of this study, cavity preparation with Er:YAG laser could be considered as a viable alternative to the conventional application of high speed handpiece and burs, which enhances the mechanical and compositional properties of lased dentin, especially when combined by subablative irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…17 demonstrated some increase in acid resistance following subablative irradiation with erbium family lasers, which failed to achieve significance in the statistical analysis, whereas Liu et al 18 and Castellan et al 19 reported a significant prevention of enamel demineralization. Morphological examination of surfaces treated by the Er:YAG laser revealed roughness and irregularities which provided microretentive patterns 12,[20][21][22][23] and at the cavity walls, there was almost no smear layer.…”
Section: Introductionmentioning
confidence: 97%
“…Then, the samples were washed with deionized water and immersed in the remineralization solution (pH = 7.0), consisting of 0.15 mol/L potassium chloride, 1.5 mmol/L calcium (CaCl 2 ), and 0.9 mmol/L phosphate ions (NaH 2 PO 4, ). 11,12 Both the demineralization and remineralization solutions were changed daily. The teeth were cycled separately in individual glass containers throughout the 14-day process, then stored in deionized water until the micro-CT scanning.…”
Section: Ph Cyclingmentioning
confidence: 99%
“…8,9 Moreover, laser irradiation produced acid-resistant surfaces by altering the calcium to phosphate ratio and promoting the formation of less soluble compounds. [10][11][12] These specific characteristics of Er:YAG laser suggest the question of whether the laser etching of enamel could be effective in preventing enamel demineralization around brackets when this technique is used routinely in clinical practice. However, it should be noted that successful orthodontic treatment depends upon the bond strengths of the orthodontic brackets.dissimilar adhesive systems.…”
mentioning
confidence: 99%
“…Reports indicate that the structural composition in enamel after irradiation with an Er:YAG laser can favor acid resistance due to the loss of carbonate [16][17][18][19][20][21]. A combination of fluoride and laser treatments can also make the enamel more resistant to acid than either treatment alone [19,20,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%